MODEL MANAJEMEN PEMBIAYAAN DAN IMPLEMENTASI HASIL RISET PADA INSTANSI PEMERINTAH YANG MENERAPKAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM (PK-BLU) - Effendi, Mohammad Sofwan (2015)
Three major problems facing Indonesian research are the research allocation budget is inadequate, research productivity is low, and the utilization of research results that have not been fullest development in Indonesia. The third problem is triggered by the current research financing mechanisms which follow the cycle of budget revenues and expenditures of the state (State Budget) and annual accounting system of the Government, so that less supports the realization of effective management and financing of research and utilization of research results to its full potential in the development of Indonesia. This research aims to develop a model of financing management and implementation of the results of research that can be applied across government agencies that implement financial management Public Service Agency (PK-BLU). Research was done at Universitas Sebelas Maret (UNS), Universitas Pendidikan Indonesia (UPI), Balai Pengkajian Teknologi Polimer (BPTP), and Lembaga Pengelola Dana Pendidikan (LPDP). The results showed has not been as effective financing mechanism and cooperation mechanism for technology transfer and commercialization of research results related to: 1) standards and selection criteria the research proposal; 2 special fees' standards in research activities; 3) research cooperation pattern); 4) monitoring and evaluation of research patterns; 5) pattern of collaboration technology transfer of research results; 6) standard management and commercialisation of research results technical requirements; and 7) tariff services and royalties as the impact of the commercialization of research results. Keywords: Resarch financing management, commersialization research output, implementation research output, public service agency. Tiga masalah utama riset yang dihadapi bangsa Indonesia adalah alokasi biaya riset yang kurang memadai, produktivitas riset yang rendah, dan pemanfaatan hasil riset yang belum maksimal dalam pembangunan Indonesia. Ketiga masalah tersebut salah satunya dipicu oleh penerapan mekanisme pembiayaan riset saat ini yang mengikuti siklus Anggaran Pendapatan dan Belanja Negara (APBN) tahunan dan sistem akuntansi pemerintah, sehingga kurang mendukung terwujudnya manajemen pembiayaan riset yang efektif dan pemanfaatan hasil riset secara maksimal dalam pembangunan Indonesia. Penelitian ini bertujuan mengembangkan model manajemen pembiayaan dan implementasi hasil riset yang dapat diterapkan di instansi pemerintah yang menerapkan Pengelolaan Keuangan Badan Lalayanan Umum (PK-BLU).Penelitian dilakukan di Universitas Sebelas Maret (UNS), Universitas Pendidikan Indonesia (UPI), Balai Pengujian Teknologi Polimer (BPTP), dan Lembaga Pengelola Dana Pendidikan (LPDP). Hasil penelitian menunjukkan belum efektifnya mekanisme pembiayaan dan mekanisme kerja sama alih teknologi dan komersialisasi hasil riset yang terkait dengan: 1) standar dan kriteria seleksi proposal riset; 2) standar biaya khusus dalam aktivitas riset; 3) pola kerja sama riset;4) pola monitoring dan evaluasi riset; 5) pola kerja sama alih teknologi hasil riset; 6)standar manajemen dan persyaratan teknis komersialisasi hasil riset; dan 7) tarif layanan dan besaran royalti sebagai dampak komersialisasi hasil riset. Kata kunci: Manajemen pembiayaan riset, komersialisasi hasil riset, implementasi hasil riset, badan layanan umum.